ASD Device Closure in Dextrocardia with Situs Inversus Totalis - Adhikari, Chandra Mani; Bogati, Amrit; Kharel, Sushant; Ghimire, Vijay; Thapa, Pratik; Yadav, Rahul; Timalsena, Birat; Saffi, Sajjad; Prajapati, Dipanker (Journal of National Heart and Lung Society Nepal, 2024)
Device closure of the atrial septal defect in dextrocardia with situs inversus totalis has been reported previously. Dextrocardia with situs Inversus totalis in ASD makes the procedure complex.With proper imaging ASD device closure can be done in such cases. We present a case of a 19 years old female, who underwent successful ASD device closure for the second time in our center.